1997
DOI: 10.1111/j.1574-695x.1997.tb01071.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of serotypes ofCampylobacter jejuniandC. colifrom Danish patients, poultry, cattle and swine

Abstract: The number of human cases of enteritis caused by Campylobacter jejuni and C. coli is increasing in Denmark and other European countries. No systemic typing has earlier been performed on Campylobacter isolates of Danish origin. The primary purpose of this study was to provide a serotype distribution of Campylobacter isolates from Danish patients and the major food production animals. In addition, the occurrence of intestinal carriers of thermophilic campylobacters among these food production animals was examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(11 citation statements)
references
References 49 publications
3
7
1
Order By: Relevance
“…We found high subtype diversity among C. jejuni isolates from cattle at each CFO, and there was no significant change in subtype diversity between or within CFOs at the arrival and interim sample times. Others have shown that C. jejuni strains present in cattle are highly genetically diverse and that a relatively small number of highly prevalent subtypes predominate (8,35,36); the findings of the current study confirm this observation across a much larger data set. We identified five CGF subtype clusters that were most prevalent among C. jejuni strains isolated from beef cattle.…”
Section: Mutation Bsupporting
confidence: 88%
“…We found high subtype diversity among C. jejuni isolates from cattle at each CFO, and there was no significant change in subtype diversity between or within CFOs at the arrival and interim sample times. Others have shown that C. jejuni strains present in cattle are highly genetically diverse and that a relatively small number of highly prevalent subtypes predominate (8,35,36); the findings of the current study confirm this observation across a much larger data set. We identified five CGF subtype clusters that were most prevalent among C. jejuni strains isolated from beef cattle.…”
Section: Mutation Bsupporting
confidence: 88%
“…However, although Jensen et al (2006) showed that the paddock environment of organic pigs was contaminated by non-pig strains, e.g., by wild fauna strains, they did not demonstrate that these strains could contaminate pigs, at least not C. jejuni strains. Pigs show a dominance of C. coli (Nielsen et al, 1997; Alter et al, 2005; Boes et al, 2005) and C. jejuni may co-exist with C. coli in pigs, but C. jejuni is typically present at in numbers that are 10–100-fold lower than C. coli (Madden et al, 2000; Jensen et al, 2005). In our study, we tested only two to three isolates per farm which may explain also why we never detected C. jejuni .…”
Section: Discussionmentioning
confidence: 99%
“…There is some host association in Campylobacter species. In a Danish survey from samples collected at abattoirs, 83%-91% of Campylobacter isolates from poultry and cattle were identified as C. jejuni, whereas 95% of isolates from swine were identified as C. coli (Nielsen, Engberg, & Madsen, 1997). In a Swedish study, C. lari was most common in migrating birds (Waldenstr€ om et al, 2002), whereas dogs are mostly colonized with C. upsaliensis (Olsson et al, 2003;Sandberg, Bergsjø, Hofshagen, Skjerve, & Kruse, 2002;Wieland et al, 2005).…”
Section: Description Of the Agent Taxonomy And Classificationmentioning
confidence: 99%